Developing Iraq's security sector : the Coalition Provisional Authority's experience - Rathmell, Andrew; Oliker, Olga.; Kelly, Terrence K.; Brannan, David W.; Crane, Keith, 1953-; Rand eBooks (Santa Monica, CA : RAND, 2005)
Following the war in Iraq, the United States and its allies found that their prewar expectations of security did not match the actual postwar environment. Iraqi security forces had largely disappeared, and those that remained were incapable of countering a rising tide of political violence and crime. From May 2003 to June 28, 2004 (when it handed over authority to the Iraqi Interim Government), the Coalition Provisional Authority (CPA) sought to field Iraqi security forces and to develop security sector institutions. This book-all of whose authors were advisors to the CPA-breaks out the various elements of Iraq$1 (Bs security sector, including the defense, interior, and justice sectors, and assesses the CPA$1 (Bs successes and failures. Furthermore, the book identifies six problems underlying the coalition$1 (Bs approach that need to be addressed if Iraq is to recover from past mistakes. Iraq needs capable security forces in the near term and sustainable security institutions for the long term. The authors emphasize that the onus must remain on the United States and its international partners to ensure that long-term institution-building remains on the Iraqi agenda.s
Introduction -- Prewar Planning for the Iraqi Security Sector -- Reforming Iraq*s Security Sector -- Evaluating Security Sector Reform in Iraq.
"RAND National Defense Research Institute."
Includes bibliographical references (p. 93-97).
Also available on the internet via WWW in PDF format.
Keywords: Civil defense -- Iraq; Law enforcement -- Iraq; National security -- Iraq; Police -- Iraq; Electronic books